Estimation of mesiodistal widths of unerupted permanent canines and premolars in the early mixed dentition period - Alireza Eshghi; Seyed Ebrahim Jabarifar; Saeid Sadeghian; Fatemeh Farahbakhshpour; Mehrnaz Aalami Harandi (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Prediction of mesiodistal widths of unerupted permanent teeth is an important aspect of space analysis during the mixed dentition period. The aim of the present study was to determine equations that can estimate the mesiodistal widths of unerupted canines and premolars of both arches in the early mixed dentition period using total widths of mandibular incisors.Materials and Methods: In this observational cross-sectional study, 100 children (50 girls and 50 boys) aged 12‒13 years in the guidance schools of Isfahan were randomly selected. The subjects had no developmental or occlusion anomalies, with no visible malformations, caries or abrasions in their teeth. After impression and preparation of dental casts, mesiodistal dimensions of all the permanent mandibular incisors, canines, and first and second premolars were measured in both arches using a Vernier caliper. Pearson's correlation coefficient, linear regression and independent t-test were applied for statistical analysis (α = 0.05).Results: Equations for this research were as follows: U = 9.295+0.549 (M), L = 6.622+0.633 (M) for girls and U = 13.4+0.38 (M), L = 11.058+0.455 (M) for boys, in which M is the total mesiodistal crown diameter of lower incisors, and U and L are the total mesiodistal crown diameters of canines and premolars in the maxilla and mandible, respectively. Statistically significant differences were observed in the total mesiodistal widths of canines and premolars between arches and genders. Correlation coefficients for the upper and lower arches were 0.76 and 0.83 in females, and 0.63 and 0.65 in males, respectively.Conclusion: Under the limitations of the present study, it can be concluded that it is possible to use regression equations to predict the mesiodistal widths of canines and premolars by measuring the total widths of permanent mandibular incisors . Key words: Analysis, Mixed dentition period, Unerupted tooth.